2019
DOI: 10.53708/hpej.v2i2.89
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Surgical Residents about Learning in Operation Theatres at CHICH Using STEEM

Abstract: Abstract Introduction: Educational environment or learning environment is a context in which teaching, training and grooming of post graduate residents occurs. Surgical specialty as a whole and operating rooms in particular are very important in terms teaching and training. Perception of residents as to this learning environment is quite vital to their learning and should be assessed objectively to identify weak and strong areas of the environment. The Surgical Theatre Educational Environment Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…Although the perception score of other subgroups are satisfactory but the difference between subgroups is statistically significant. Consistent with other studies 10,11 this study also shows females are less satisfied than males (19.92±4.92/40 vs 21.48±5.54/40) regarding the perception of the most crucial factor (group D) i.e. supervision and support by the faculties or the system.…”
Section: Discussionsupporting
confidence: 92%
“…Although the perception score of other subgroups are satisfactory but the difference between subgroups is statistically significant. Consistent with other studies 10,11 this study also shows females are less satisfied than males (19.92±4.92/40 vs 21.48±5.54/40) regarding the perception of the most crucial factor (group D) i.e. supervision and support by the faculties or the system.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also reported similarly positive scores for the “teaching and training” subscale. However, the “learning opportunities” subscale has been positively reported in other studies with mean scores of 72.6% and 76.21% [ 15 , 22 ].…”
Section: Discussionmentioning
confidence: 93%
“…9 “Before the operation my consultant discusses what part of the procedure I will perform.” Nagraj also had similar findings with no significant difference in the Overall score, between male and female responders, however, female residents perceived a much more positive operating theatre educational environment (score of 176) than did their male colleagues (score 153) [ 23 ]. Other studies did not indicate the presence of any difference in the total or any of the subscales based on gender [ 13 , 22 ]. The causes of this disparity were not determined in this study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations